Legal Gaps and Socio-Legal Realities in the Protection of Indigenous Papuan (OAP) Workers - Sassan, Jonhi; Sakmaf, Marius Suprianto (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The implementation of policies aimed at protecting and empowering Indigenous Papuan (OAP) workers in West Papua remains suboptimal, despite the existence of a special autonomy framework and affirmative action measures. This study seeks to examine the roles and responsibilities of local governments and to identify the factors affecting the effectiveness of these policies. The research employs a normative legal approach, incorporating statutory and conceptual analyses, and is supported by qualitative methods. The findings reveal that key constraints include inadequate infrastructure, limited institutional capacity, insufficient human resources, and weak integration between formal legal systems and customary law. It is concluded that enhancing policy effectiveness requires a holistic, participatory, and context-sensitive approach to ensure the protection and empowerment of Indigenous Papuan workers.